Urban Screens : Situations, Practices, Concepts - Nanna Verhoeff (Routledge, 2025)
This book offers a discussion of the screens, installations, and media architecture that populate contemporary urban public spaces. It proposes a methodological approach and conceptual toolset for the critical examination, not only of what these screens do, but also of what we can do with them. The book contains a collection of theoretical concepts, developed through an in-depth examination of the material, relational, and performative aspects of a range of urban screens and screen practices. Its situational and practice-oriented approach focuses on the space between their material surfaces, the spectatorial situations they create, and how such screens situate us in relation to the surrounding social and cultural environment of the city. Offering concepts for a critical understanding of the wide variety of contemporary urban screen practices, the book's methodological proposal integrates close situational analyses and a historical-comparative approach for individual screens and screening situations in their role as part of a wider global contemporary screen culture.